New Malolactic Bacteria Strains Isolated from Wine Microbiota: Characterization and Technological Properties - Răzvan Vasile Filimon; Claudiu-Ioan Bunea; Ancuța Nechita; Florin Dumitru Bora; Simona Isabela Dunca; Andrei Mocan; Roxana Mihaela Filimon (Fermentation, 2022)
Malolactic fermentation (MLF) or biological decrease of wine acidity is defined as the enzymatic bioconversion of malic acid in lactic acid, a process performed by lactic acid bacteria (LAB). The procedures for the isolation of new indigenous LAB strains from the red wines produced in Copou Iasi wine center (NE of Romania) undergoing spontaneous malolactic fermentation, resulted in the obtaining of 67 catalase-negative and Gram-positive LAB strains. After testing in the malolactic fermentative process, application of specific screening procedures and identification (API 50 CH), two bacterial strains belonging to the species Oenococcus oeni (strain 13-7) and Lactobacillus plantarum (strain R1-1) with high yield of malolactic bioconversion, non-producing biogenic amines, and with active extracellular enzymes related to wine aroma, were retained and characterized. Tested in synthetic medium (MRS-TJ) for 10 days, the new isolated LAB strains metabolized over 98% of the malic acid at ethanol concentrations between 10 and 14 % (v/v), low pH (>3.0), total SO2 doses up to 70 mg/L and temperatures between 15 and 35 °C, showing high potential for future use in the winemaking process as bacterial starter cultures, in order to obtain high quality wines with increased typicity.